Is the Theistic Multiverse Incoherent?: A Reply to Michael Almeida - Donahue, Miles K. (Philosophia (Ramat Gan), 2025)
Several philosophers contend that a theistic multiverse (TM), a collective of all possible universes worthy of divine creation, is the best possible world, and that this fact proves helpful to theism in the face of various objections. Almeida (2017), however, argues that proposed theories of TM are incoherent. After presenting TM, I distinguish three objections Almeida raises against it: God cannot create universes corresponding to other possible worlds, we cannot know whether TM includes only worthwhile universes, and TM violates the principle of plenitude. I show that none of these undermine TM’s potential to address various objections to theism.